Designing MOOCs with VMS (Virtual Microscopic Simulation) for Measurement Student’s Level Understanding (LU) - Sisi Saptria Dewi; Suherman Suherman; Firmanul Catur Wibowo; Dina Rahmi Darman; Aji Pancer Agung Rino; Ilham Akbar Darmawan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
The aims of this research to design Massive Online Open Courses (MOOCs) from now on referred to as Virtual Microscopic Simulation (VMS) to measure the Level Understanding (LU) of the construction of microscopic phenomena electric-field conceptions. The research method used is a mixed-method using embedded design. The research subjects are high school students, and one of the universities in Banten Province. The results of this study are software with features in the form of MOOCs-VMS that are categorized very well based on expert judgment on aspects of usability and learning content. The average score of media expert validation score is 96% with a very feasible category, the average score for material expert validation is 98% with a very decent category, and the average user response rate is 86% with a very good category. It can be concluded that the design of MOOCs-VMS can be used as an alternative media for conducting distance learning and is significant in building the level of understanding students.